2021
DOI: 10.24110/0031-403x-2021-100-6-23-31
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Children Associated With Covid-19: Results of a Multicenter Study

Abstract: Coronavirus disease 2019 (COVID-19) in children in most cases is asymptomatic or mild, and its most severe late complication is multisystem inflammatory syndrome in children (MIS-C). The aim of the study is to find clinical, laboratory and instrumental characteristics, description of therapeutic tactics, including determination of the profile of patients requiring Tocilizumab prescription and the outcomes of MIS-C associated with COVID-19. Materials and methods of research: 245 children aged 3 months – 17 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Russian scientists have noted that in boys, the course of MIS-C was also the most severe in 57% of cases. The syndrome was diagnosed in 64% of children of the Eastern European population, but there was no correlation with the severity of MIS-C [ 21 ]. The conducted studies showed the significance of an increase in ESR in 69%, procalcitonin in 69%, ferritin in 77%, and CRP in 98% [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Russian scientists have noted that in boys, the course of MIS-C was also the most severe in 57% of cases. The syndrome was diagnosed in 64% of children of the Eastern European population, but there was no correlation with the severity of MIS-C [ 21 ]. The conducted studies showed the significance of an increase in ESR in 69%, procalcitonin in 69%, ferritin in 77%, and CRP in 98% [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It described results where 245 children with MIS-C were treated. Their age ranged from 3 months to 17 years [ 21 ]. It was shown that patients had damage to the cardiovascular system (66%), as well as gastrointestinal disorders (61%), every fourth patient had neurological disorders (27%) and signs of respiratory failure (19%).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of monoclonal antibody therapy may be related to the severity of presentation, but this is generally unclear from the papers reviewed 29 . In a study by Novikova et al, they found that children receiving monoclonal antibodies experienced a severe course of disease compared to patients who were not administered monoclonal antibodies 22 . The choice of population in which monoclonal antibodies are used may therefore skew our understanding of the e cacy and outcome of their use.…”
Section: Discussionmentioning
confidence: 99%
“…Rationale for monoclonal antibody therapy was MIS-C refractory to the initial therapy of IVIG and steroids [14][15][16][17][18][20][21][22][23][24][25][26][27][29][30][31] . Very rarely were monoclonal antibodies utilized as rst line therapy.…”
Section: Monoclonal Antibody Therapy Rationalementioning
confidence: 99%
See 1 more Smart Citation